Not getting a word in edgeways? Language, gender, and identity in a British comedy panel show. (September 2016) - Lawson, Robert; Lutzky, Ursula
Abstract: Despite the great strides made over the past 30 years by female comedy performers, their status in a male-dominated industry has typically been marginal. This is coupled with the widespread view that even women who do appear on mainstream comedy face the challenge of getting their voices heard in an arena where it is often the loudest voice that wins. In order to investigate claims that female comedians contribute less than male comedians on comedy panel shows, this article presents the findings of a sociolinguistic analysis of the British show Mock the Week, drawing on an XML-annotated corpus of the transcripts of series five. Rather than viewing features such as talkativeness and interruption solely as a substantiation of conversational dominance (cf.Brand, 2009 ), we suggest that these can also be understood as strategies in the production of humour in the context of comedy panel shows. In addition to genre-specific considerations, our results show that the use of these features on Mock the Week is influenced by an interplay of social factors, rather than gender alone. Overall, this study could act as a catalyst for writers and production companies to use more linguistically-informed approaches to comedy show scripting, particularly in relation to issues of linguistic and representational inequality. Highlights: We examine language use in the mainstream British comedy show Mock the Week. Article challenges common perceptions of gender and language use in the show. Results outline a complex interplay of speaker role and speaker sex in the construction of comedic interactions. Offers recommendations to industry about tackling inequalities of representation and participation in the comedy industry.